2017
DOI: 10.1188/17.cjon.e272-e279
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Self-Efficacy: A Concept Analysis for Symptom Management in Patients With Cancer

Abstract: Greater PSE for symptom management predicts improved performance outcomes, including functional health status, cognitive function, and disease status. Clarification of the concept of PSE for symptom management will accelerate the progress of self-management research and allow for comparison of research data and intervention development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 50 publications
0
31
0
9
Order By: Relevance
“…Using the PROMIS S-E tool, this study showed opportunity to improve AYAs' self-efficacy to manage symptoms. As with AYA cancer survivors 7 and adults with cancer, 29 improved self-efficacy may translate into improved symptom outcomes, which were not examined in this study, but are important variables for future symptom selfmanagement studies.…”
Section: Discussionmentioning
confidence: 99%
“…Using the PROMIS S-E tool, this study showed opportunity to improve AYAs' self-efficacy to manage symptoms. As with AYA cancer survivors 7 and adults with cancer, 29 improved self-efficacy may translate into improved symptom outcomes, which were not examined in this study, but are important variables for future symptom selfmanagement studies.…”
Section: Discussionmentioning
confidence: 99%
“…White et al [22] analysed the concept of selfefficacy in relation to symptom management in patients with cancer. If cancer patients are not able to manage their symptom, the outcomes would be increased symptom distress, poor prognosis, decreased quality of life (QoL) and survival [23].…”
Section: Concept Analyses Of Self-efficacymentioning
confidence: 99%
“…If cancer patients are not able to manage their symptom, the outcomes would be increased symptom distress, poor prognosis, decreased quality of life (QoL) and survival [23]. White et al [22] also used Walker's and Avant [19] concept analysis method to determine the antecedents, defining attributes and consequences. For the patients with cancer, the attributes of self-efficacy are cognitive, affective processes, motivation, confidence, competence and awareness of how they perceive and evaluate the symptoms.…”
Section: Concept Analyses Of Self-efficacymentioning
confidence: 99%
“…However, successful beliefs in taking nanogold and nanosilver medication need to be investigated. To receive the disease is self-regulated [1]. This self-regulated deals with quality of life, functional status, and health care.…”
Section: Introductionmentioning
confidence: 99%